Réponse :
Explications étape par étape
Bonsoir
Racines des polynômes :
P1(x) = -8x^2 + 4x + 2
[tex]\Delta = 4^{2} - 4 \times -8 \times 2 = 16 + 64 = 80[/tex]
[tex]\sqrt\Delta = 4\sqrt5[/tex]
[tex]x_{1} = (-4 - 4\sqrt5)/(2 * -8) = (1 + \sqrt5)/4[/tex]
[tex]x_{2} = (-4 + 4\sqrt5)/(-16) = (1 - \sqrt5)/4[/tex]
P2(x) = 3x^2 - 5x + 1
[tex]\Delta = 5^{2} - 4 \times 3 \times 1 = 25 - 12 = 13[/tex]
[tex]\sqrt\Delta = \sqrt13[/tex]
[tex]x_{1} = (5 - \sqrt13)/(2 * 3) = (5 - \sqrt13)/6[/tex]
[tex]x_{2} = (5 + \sqrt13)/6[/tex]
P3(x) = x^2 - x + 1
[tex]\Delta = (-1)^{2} - 4 \times 1 \times 1 = 1 - 4 = -3[/tex] < 0 pas de solution
P4(x) = 3x^2 + 5x - 2
[tex]\Delta = 5^{2} - 4 \times 3 \times -2 = 25 + 24 = 49[/tex]
[tex]\sqrt\Delta = 7[/tex]
[tex]x_{1} = (-5 - 7)/(2 * 3) = (-12)/6 = -2[/tex]
[tex]x_{2} = (-5 + 7)/(6) = 2/6 = 1/3[/tex]
Forme canonique :
P5(x) = 2x^2 + 8x + 8
P5(x) = 2(x^2 + 4x + 4)
P5(x) = 2(x + 2)^2
P6(x) = 3x^2 - 18x + 21
P6(x) = a(x - α)^2 + β
Avec :
α = - b/(2a) = 18/(2 * 3) = 18/6 = 3
β = (b^2 - 4ac)/(4a) = ((-18)^2 - 4 * 3 * 21)/(4 * 3) = (324 - 252)/12 = 6
P6(x) = 3(x - 3)^2 + 6